UK midwives delivering physical activity advice; what are the challenges and possible solutions? - Mitra, Marina; Marino, Katherine; Vishnubala, Dane; Pringle, Andy; Nykjaer, Camilla (Frontiers in Sports and Active Living, 2024)
Despite physical activity (PA) providing specific health benefits during pregnancy and the postpartum period, many women report decreased PA during this time. Provision of PA advice has been found to be lacking amongst midwives due to a range of barriers. This study aimed to evaluate United Kingdom's midwives' current role and knowledge regarding the provision of PA advice to pregnant and postpartum women and identify the barriers and potential solutions. Ten UK midwives (mean work experience ± SD: 15.5 years ± 10.2) participated in semi-structured interviews between May and July 2023. Data were analysed using a deductive thematic approach following Braun and Clarke's six steps. Demographic data were collected by Microsoft Forms then summarised using Microsoft Excel. Six themes with 25 subthemes were identified as barriers and solutions in delivering PA advice. The role of midwives in providing PA advice during pregnancy; the role of midwives in providing PA advice postpartum; intrinsic barriers that limit PA advice provision (confidence, safety concerns, knowledge, and midwife's personal body habitus); extrinsic barriers that limit PA advice provision (lack of time, education, PA not a priority in care); solutions to allow midwives to promote PA (including formal PA education, and dissemination of resources); and optimising delivery of PA advice (personalized approach, interprofessional collaboration, and linking to mental health benefits).Midwives consider themselves ideally placed to provide PA advice to pregnant women, with many aware of the benefits PA provides. Despite this, there is a lack of PA advice provision and knowledge of PA guidelines. Postpartum PA advice appeared to be considered outside the remit of midwives, due to limited contact. Further research is needed to determine the current level of PA advice provision for pregnant and postpartum women and explore the role of other healthcare professionals involved in maternity care.